Pengaruh Fear of Missing Out (FoMO), Price Discount, dan In-Store Display Terhadap Impulse Buying Fresh Food Pada Lawson Surabaya - Awaliyah, Hilyatul; Chrismardani, Yustina (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
This study aims to determine the effect of Fear of Missing Out (FoMO), Price Discount, and In-Store Display on Impulse Buying Fresh Food at Lawson Surabaya. The sample in this study was taken from Lawson consumers using purposive sampling method and obtained 100 consumers as the observed sample. The analysis technique in this study used Structural Equation Modeling (SEM) analysis with the help of the SmartPLS 4.1 statistical programme. The results showed that Fear of Missing Out (FoMO) has a positive and insignificant effect on impulse buying, price discount has a positive and significant effect on impulse buying, in-store display has a positive and significant effect on impulse buying.